Structure-guided engineering of type I-F CASTs for targeted gene insertion in human cells - George D. Lampe; Ashley R. Liang; Dennis J. Zhang; Israel S. Fernández; Samuel H. Sternberg (Nature Communications)
Abstract Conventional genome editing tools rely on DNA double-strand breaks (DSBs) and host recombination proteins to achieve large insertions, resulting in heterogeneous mixtures of undesirable outcomes. We recently leveraged a type I-F CRISPR-associated transposase, PseCAST, for DSB-free DNA integration in human cells, albeit at low efficiencies; multiple lines of evidence suggest DNA binding may be a bottleneck for higher efficiencies. Here we report structural determinants of DNA recognition by the PseCAST QCascade complex using single-particle cryogenic electron microscopy (cryoEM), revealing subtype-specific interactions and RNA-DNA heteroduplex features. By combining structural data, library screens, and rationally engineered mutants, we uncover variants with increased integration efficiencies and modified PAM stringencies. We further leverage transpososome structural predictions to build hybrid CASTs that combine orthogonal DNA binding and integration modules. Our work provides unique structural insights into type I-F CASTs and showcases diverse strategies to investigate and engineer RNA-guided transposase architectures for human genome editing applications.